Working together : why great partnerships succeed - Eisner, Michael, 1942-; Cohen, Aaron, 1978- (New York : Harper Business, 2010)
In this fascinating look at why great partnerships succeed, former Disney CEO Michael Eisner discusses how professional partnerships have contributed to his success. In addition, Eisner tells the stories of nine other highly successful business collaborations.--From publisher description.
Keywords: Strategic alliances (Business).; Partnership; Success in business